Wind-induced response analysis of wind turbine tubular towers with consideration of rotating effect of blades. Issue 2 (January 2020) - Huo, Tao; Tong, Lewei
This study discusses the wind-induced response of existing pitch-controlled 1.25 MW wind turbine structures, with a particular focus on the influence of the blade-rotation effect, cross-wind loads of the tubular tower and the wind direction, and compares numerical responses with the measured dynamic responses. An integrated finite-element model consisting of blades, a nacelle, a tower and a foundation is established. The aerodynamic loads exerted on the rotating blades and the aerodynamic loads acting on the tubular tower are then obtained. A wind-induced response calculation method of the wind turbine structures corresponding to different wind speeds and wind directions is established for performing a wind-induced response analysis. Finally, comparisons between the measured responses and the corresponding numerical response results are performed to verify the accuracy of the proposed wind-induced response calculation method. The results indicate that neglecting the cross-wind aerodynamic loads of large-scale wind turbine structures can lead to unsafe design. The wind direction has different influences on the along-wind and cross-wind dynamic responses. The statistical values of the measured dynamic responses are slightly greater than those of the numerical analysis results, but the magnitudes of the responses are the same. Therefore, the proposed wind-induced response calculation method for wind turbine structures is feasible and reasonable. It can be used to conduct the fatigue life prediction of wind turbine tubular towers in future research which is an important issue in the structural design of wind turbine tubular tower structures.